Negative impact of online gambling problematic in disabled and non-disabled university students: exploring the risk profile - Suriá-Martínez, Raquel; García-Castillo, Fernando; Villegas-Castrillo, Esther; López-Sánchez, Carmen; Carretón-Ballester, Carmen (Frontiers in Psychology, 2024)
This research examines the gambling profile and beliefs of university students based on whether they have a disability. In turn, it seeks to identify if there is a typology of at-risk gamblers according to the disability variable. Finally, it aims to find out the prevalence of gambling among students depending on whether they have a disability and the typology of at-risk gambler. A total of 704 university students (135 with disabilities and 569 without disabilities) completed the NODS Belief Questionnaire (1999) to assess problems associated with gambling and to generate a typological grouping of risk gamblers, as well as a questionnaire designed specifically for the gambler profile. It was found that a small percentage of participants engage in gambling on a daily basis, with a higher frequency among students with disabilities. In addition, it was observed that the behaviour and concern about financial expenditure on gambling interferes with their daily activities and is a cause for concern, with higher risk being observed to a greater extent in students with disabilities. These data suggest the importance for universities and relevant authorities to address these problems comprehensively, providing adequate resources for students with disabilities and promoting a culture of wellbeing that discourages problematic gambling activities and encourages healthy alternatives for entertainment and stress management.